The commitment of packaging industry in the framework of the European strategy for plastics in a circular economy - Eleonora Foschi; Alessandra Bonoli (Administrative Sciences, 2019)
European Commission is strongly committed into issues related to plastic materials production and plastic waste management. While the Circular Economy Package has set targets generally referred to recycling rates, the European Strategy for plastics in a circular economy (and related action plan), fosters sustainability along the entire plastic value chain: from primary producers to converters, brand owners and retailers to waste collectors and recyclers. The Directive on the reduction of the impact of certain plastic products on the environment (more commonly known as Directive on Single-Use-Plastics, waiting for publication in the Official Journal of the European Union) rules targets on ten plastic products most often found as littering on global beaches, directly affecting plastic industry and, consequently, market. Policy makers and industrial stakeholders are called upon to collaborate. The article aims to illustrate interactions between European Commission and all plastic value chain stakeholders on implementing measures to reach ambitious targets pursued by the recent European policy. The study shows how European Commission has robustly worked to regulate production and consumption patterns on plastic carrier bags and packaging (including food packaging) thus facilitating the achievement of specific targets provided by the recent Directive. However, additional provisions concerning market restriction have been introduced; industrial stakeholders carried on a prompt response by promoting the creation of alliances, join venture and association, as well as a more integrated plastic value chain. On the base of this purpose, a virtuous example of a closed supply chain is presented.
Keywords: 350; plastic; circular economy; European Strategy for Plastics in a Circular Economy; Single-Use-Products; environmental management; closed-loop supply chain